Multichannel ARINC429 bus test system based on FPGA - Sun Ao; Qin Xujun (Dianzi Jishu Yingyong, 2023)
ARINC429 bus is one of the aviation communication buses. It has the characteristics of high reliability and strong anti-interference ability, and is widely used in the aviation industry. This paper designs a multi-channel ARINC429 bus board with FPGA as the main control chip and bus interface chip. The purpose is to achieve automated testing and provide testing efficiency. This paper focuses on the design of FPGA, the application of interface chip and architecture design. Finally, the timing of the selected interface chip, the actual signal quality of ARINC429 bus and the overall function of the system are tested. The actual test shows that the board can communicate reliably at different rates and the data is stable.